Exergy-based Control of a Dwelling Ventilation System with Heat Recovery (Моделювання, керування та інформаційні технології, 2019)
On the base of exergy-based approach it is shownthat for the ventilation systems there are operating modes forwhich heat recovery increases exergy of fuel expended to providethe ventilation air compared to cases without bringing anyrecovery of heat and additional power consumption to drive theair flow by the fans. For the specified system, in case of switchingventilation unit to the operation mode of lower values of spentfuel exergy it is possible to provide annual saving from 5 to 15 %of the primary energy sources.